Risk Factors of Atrial Arrhythmia in Patients With Liver Cirrhosis: A Retrospective Study - Lu, Xiya; Wang, Zhijing; Yang, Liu; Yang, Changqing; Song, Meiyi (Frontiers in Cardiovascular Medicine, 2021)
Background and Objectives: Liver cirrhosis is known to be associated with atrial arrhythmia. However, the risk factors for atrial arrhythmia in patients with liver cirrhosis remain unclear. This retrospective study aimed to investigate the risk factors for atrial arrhythmia in patients with liver cirrhosis. Methods: In the present study, we collected data from 135 patients with liver cirrhosis who were admitted to the Department of Gastroenterology at Shanghai Tongji Hospital. We examined the clinical information recorded, with the aim of identifying the risk factors for atrial arrhythmia in patients with liver cirrhosis. Multiple logistic regression analysis was used to screen for significant factors differentiating liver cirrhosis patients with atrial arrhythmia from those without atrial arrhythmia. Results: The data showed that there were seven significantly different factors that distinguished the group with atrial arrhythmia from the group without atrial arrhythmia. The seven factors were age, white blood cell count (WBC), albumin (ALB), serum Na+, B-type natriuretic peptide (BNP), ascites, and Child-Pugh score. The results of multivariate logistic regression analysis suggested that age (β = 0.094, OR = 1.098, 95% CI 1.039–1.161, P = 0.001) and ascites (β =1.354, OR = 3.874, 95% CI 1.202–12.483, P = 0.023) were significantly associated with atrial arrhythmia. Conclusion: In the present study, age and ascites were confirmed to be risk factors associated with atrial arrhythmia in patients with liver cirrhosis.